Implementation of the Community Policing Program in (Problem Solving) Minor Crimes (Case Study of Lubuk Pakam Police) - Wardhani Syahputri, Vita Aliyana; Harahap, Mar'ie Mahfudz (LEGAL BRIEF, 2024)
This research aims to determine the legal regulation of the community policing program in (problem solving) minor crimes, the implementation of the community policing program in realizing restorative justice in minor crimes at the Lubuk Pakam police station, and to find out what the challenges and obstacles are in implementing the community policing program in (problem solving) offenses. light crime at Lubuk Pakam Police. The results of the research show that in practice the implementation of the community policing program is in accordance with applicable procedures as regulated by the Republic of Indonesia Regulation No. 3 of 2015 concerning Community Policing. However, the output of the problem solving obtained did not result in peace, because Bhabinkantibmas as the mediator was unable to mediate and provide a win-win solution between the two parties. So there are many cases of minor criminal offenses at the Lubuk Pakam Police which fail in Restorative justice efforts. The obstacles and challenges experienced by the Lubuk Pakam Police in implementing the community policing program include Bhabinkantibmas human resources who do not master the problem solving approach and the community's mindset is still layman about current legal developments